Liberação do túnel do tarso pela tecnica endoscópica : uma proposta de acesso cirúrgico - Bezerra, Marcelo José Cortez (2005)
Establish two portals in cadaver specimens, using anatomical delimitation points and geometrical lines, which allow the access to the tarsal tunnel by the video-endoscopic technique and the comparison between the proximal-distal direction approach with the reverse one. This trial has included 18 cadavers and 36 ankles were the total amount that was studied. Starting with the biportal endoscopic technique, initially described and modified in this trial through geometrical lines and anatomical points delimitation, the tarsal tunnel was released in left ankles with the insertion of instruments using proximal-distal direction and the opposite to the right ankles. There were, in the right ankles, complete section of flexor retinaculum in 15 cases (83,3%) and partial section in 3 cases (16,67%). In the left ankles there were complete section of flexor retinaculum in 16 (88,89%) and partial section in 2 cases (11,11%). The average operative time was 19,44 minutes for the right limb and 18,33 minutes for the left limb. No damage to neurovascular structures has been observed in any case. According to the suggested technique, the total section of flexors retinaculum was obtained in all the cases after learning curve period without lesion of anatomical structures in the tarsal tunnel, independent of whatever be the direction chosen in the access way.